EFEKTIVITAS PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN IBU TENTANG PEMBERIAN ASIEKSKLUSIF PADA BAYI 0-6 BULAN DI PUSKESMAS BABULU KABUPATEN MALAKA - Moruk, Maria Alince; Letor, Yulia M. K.; Yasintha Goa, Maria (STIKes CHMK, 2024)
Child health is one of the main problems in the health sector in Indonesia. The causes of high infant mortality in Indonesia are congenital disorders, sepsis, upper respiratory tract infections, nutritional and environmental factors. One of the nutritional factors is the exclusive breastfeeding of the baby. The low level of exclusive breastfeeding by breastfeeding mothers can be caused by many factors, namely education, age, occupation, parity, socioeconomic, and family support. In addition, the factor that influences the success of coverage or exclusive breastfeeding for infants aged 0-6 months is knowledge. The purpose of this study was to analyze the effectiveness of health education on maternal knowledge about exclusive breastfeeding for infants 0-6 months at the Babulu Community Health Center. This research is a quantitative study using a quasi-experimental research design non-randomized with a pre and post test design without control. The population is all mothers who have babies aged 0-6 months and pregnant women in the 2nd and 3rd trimesters with a total sample of 50 people. The sampling technique used is purposive sampling technique with data collection using questionnaire sheets pre and post test and data analysis using statistical test dependent T test (paired t-test). Based on the results of statistical tests, the results obtained p value = 0.000 less than alpha = 0.05, (p <0.05). This means that there are differences in the knowledge of mothers before and after being given health education. As for the advice given to mothers who have babies aged 0-6 months, they are supposed to follow the counseling given by health workers regarding the importance of exclusive breastfeeding so that there are no more mothers who do not provide exclusive breastfeeding to their babies. Keywords : Health Education, Knowledge, Exclusive Breastfeeding